2018
DOI: 10.1111/eos.12577
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent aphthous stomatitis and gene variability in selected interleukins: a case–control study

Abstract: Genetic factors, especially those related to immune system functioning, have been intensively studied to determine their role in the development of recurrent aphthous stomatitis (RAS). The aim of the present study was to analyze gene variability in interleukin (IL)2, IL4 (and its receptor α, IL4Rα), IL10, and IL13, which were selected based on literature review and/or their functional relevance, in Czech patients with RAS and in healthy controls. In total, 252 subjects (178 controls and 74 patients with RAS) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…Several cytokines that are linked with RAS pathogenesis have also been studied, however there were no confirmatory observations on those cytokines in RAS. Clinical studies that focused on estimation of cytokine levels in RAS are interferon and Interleukins, such as IFN [34,35], IL-8 [36], IL-1β [37][38][39][40], IL-1 [35,41,42], IL-2 [34,[43][44][45][46], IL-4 [44,45,47,48], IL-6 [37,42,46,49], 45,[50][51][52][53], IL-12 [50,51], IL-13 [35,45], IL-17 [35,54], IL-17C [55], IL-17F [56]. Unfortunately, these findings on cytokines were not able to achieve any clinically reliable application in RAS while comparing TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines that are linked with RAS pathogenesis have also been studied, however there were no confirmatory observations on those cytokines in RAS. Clinical studies that focused on estimation of cytokine levels in RAS are interferon and Interleukins, such as IFN [34,35], IL-8 [36], IL-1β [37][38][39][40], IL-1 [35,41,42], IL-2 [34,[43][44][45][46], IL-4 [44,45,47,48], IL-6 [37,42,46,49], 45,[50][51][52][53], IL-12 [50,51], IL-13 [35,45], IL-17 [35,54], IL-17C [55], IL-17F [56]. Unfortunately, these findings on cytokines were not able to achieve any clinically reliable application in RAS while comparing TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Kalpana et al identified increased salivary levels of IL-2 in patients with RAS [132], while other researchers did not reveal significant differences between serum levels of IL-2 in patients with RAS, compared to controls [132][133][134][135]. The explanation for these differences is not very clear.…”
Section: Relationships Between Fa and Recurrent Aphthous Stomatitismentioning
confidence: 93%
“…To test this hypothesis and to limit any confounding bias (latitude, etc. ), we focused on the countries whose IL‐6 gene polymorphisms at rs1800796 and rs1800795 loci, IL‐6R gene polymorphism at rs2228145 locus, IL‐10 gene polymorphism at rs1800896 and rs1800871 loci, IL‐17A gene polymorphism at rs2275913 and IL‐17F gene polymorphism at rs763780 loci were defined and the allele frequencies were reported in 54 studies 10–63 . We searched the literature for the interleukin gene polymorphisms determined in the populations of China, Japan, India, Spain, Mexico, Sweden, Turkey, Brazil, Russia, Poland, Italy, South Africa, Netherlands, Greece, Germany, UK, Iran, Finland, Czechia, Tunisia, Norway, Egypt, Croatia.…”
Section: Methodsmentioning
confidence: 99%